Nanofibers and nanotechnology in textiles - Brown, P. J. 1963-; Stevens, K. 1976- (Woodhead publishing in textiles., 2007)
Nanotechnology is revolutionising the world of materials. This important book reviews its impact in developing a new generation of textile fibers with enhanced functionality and a wide range of applications. The first part of the book reviews nanofiber production, discussing how different fiber types can be produced using electrospinning techniques. Part two analyses the production and properties of carbon nanotubes and polymer nanocomposites and their applications in such areas as aerospace engineering. The third part of the book considers ways of using nanotechnology to improve polymer properties such as thermal stability and dyeability. The final part of the book reviews the use of nanotechnology to modify textile surfaces, including the use of coatings and films, in order to improve hydrophobic, filtration and other properties. Nanofibers and nanotechnology in textiles is a valuable reference in assessing and using a new generation of textile fibers in applications as diverse as tissue and aerospace engineering. Nanotechnology is revolutionising the world of materialsLearn about a new generation of textile fibers that have a wide range of applicationsExamines how to improve polymer properties.